Cultural Impact on the Intention to Use Nursing Information Systems of Nurses in Taiwan and China: Survey and Analysis - Chang, I-Chiu; Lin, Po-Jin; Chen, Ting-Hung; Chang, Chia-Hui (JMIR Publications, 2020)
BackgroundNursing workforce shortage has emerged as a global problem. Foreign nurse importation is a popular strategy to address the shortage. The interactions between nursing staff on either side of the Taiwan Strait continue to increase. Since both nurses in Taiwan and nurses in China have adopted nursing information systems to improve health care processes and quality, it is necessary to investigate factors influencing nursing information system usage in nursing practice. ObjectiveThis study examined the effects of cultural and other related factors on nurses' intentions to use nursing information systems. The findings were expected to serve as an empirical base for further benchmarking and management of cross-strait nurses. MethodsThis survey was conducted in two case hospitals (one in Taiwan and one in China). A total of 880 questionnaires were distributed (n=440 in each hospital). ResultsThe results showed effort expectancy had a significant effect on the intention to use nursing information systems of nurses in China (P=.003) but not nurses in Taiwan (P=.16). ConclusionsFindings suggest nursing managers should adopt different strategies to motivate cross-strait nurses to use nursing information systems. Promoting effort expectancy is more likely to motivate nurses in China than in Taiwan. This discrepancy is probably due to the less hierarchical and more feminine society in Taiwan.